Abernethy Malformation in Children with Focal Liver Lesions - D. E. Arutyunyants; V. V. Khovrin; T. N. Galyan; A. S. Kulichkin; A. V. Filin; E. Yu. Kryzhanovskaya (Вестник рентгенологии и радиологии)
Abernethy malformation is a congenital disease characterized by complete or partial underdevelopment of the portal vein, leading to the occurrence of congenital extrahepatic portosystemic shunts. The anomaly with the absence of the portal vein is detected in 80% of cases in childhood. Patients with this pathology are very frequently examined when detecting space-occupying liver lesions and assuming the presence of a vascular abnormality. The paper describes clinical cases of benign focal liver lesions and Abernethy malformation in children.